The clinical importance of serrated lesions of the colorectum - Burke, Carol (2017)
Colorectal cancer (CRC) is the third most common cancer in the world. Fortunately, it is also proven to be one of the most preventable cancers, in large part due to the utilization of CRC screening. Historically, it was believed that the adenomatous polyp was the only precursor to carcinoma of the colorectum. Within the last decade, it has been shown that approximately 20-30% of sporadic colon cancers arise through a distinct molecular pathway called CpG Island Methylation (CIMP) which is due to widespread DNA methylation. There is strong evidence that serrated polyps are the precursor lesions for colon cancers arising through the CIMP pathway.